Entrepreneurial Leadership Values in Tourism Classroom Teaching. Enhancing the Learning Processes for Tourism Business - FAHRURROZI, Muh.; WATHONI, Hamzani; BASRI, Hasan; MOHZANA, Mohzana; DWIMAULANI, Astrid (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023, 2023)
Leadership has long been studied cross academic and non-academic. Since it influences a robust learning outcome, schools should seriously incorporate leadership in the curriculum of study program. Leadership teaching in the tourism class, however, is overlooked and less practiced. Therefore, this research aims at elaborating an effective teaching course in the tourism class by adopting entrepreneurial leadership (motivation, visioner, proactive, ability to spot opportunity, courage, innovation, and creativity) for activities from tourism sector. Using participatory action research, entrepreneurial leadership is taught to the third semester of college students of tourism discussing marketing. There were 44 sample sizes taken with purposive sampling. As a key instrument, the researcher evaluates group discussion notes to achieve indicators of readable content and conclude with a profound summary. Findings show that teaching successfully implemented the values of entrepreneurial leadership in the tourism classroom. All activities were reflected on warming up to discussion, group discussion notes, and presentation performance within three-day-teaching.